DNA Nanodevices: Electronic Activation of a DNA Nanodevice Using a Multilayer Nanofilm (Small 40/2016). Issue 40 (October 2016) - Jeong, Hyejoong; Ranallo, Simona; Rossetti, Marianna; Heo, Jiwoong; Shin, Jooseok; Park, Kwangyong; Ricci, Francesco; Hong, Jinkee
Abstract : A nonconventional strategy in DNA nanodevice activation is determined by F. Ricci, J. Hong, and co‐workers on page 5572, using a graphene and DNA based electro‐responsive multilayer nanofilm by means of layer‐by‐layer assembly. The nanofilm onto a chip‐electrode controls spontaneous conformational change of the DNA nanodevice via controlled release of complementary strands as a trigger, depending on electronic inputs including reductive potentials that allow efficient activation of a DNA nanodevice.